Percutaneous Cystic Duct Stenting: Report of Two Cases - Shouvik Paul; Anupam Singh; Santosh Irrinki; Divya Dahiya; Pankaj Gupta (Journal of Clinical Interventional Radiology ISVIR)
Percutaneous cholecystostomy involves the placement of a catheter in the gallbladder via image-guided puncture through either a transhepatic or a transperitoneal route. It is most commonly utilized for managing patients with moderate to severe acute cholecystitis who are otherwise unfit for immediate surgery. While the procedure has a high technical success rate, there is significant morbidity, mainly due to catheter-related issues. Endoscopic ultrasound (EUS) guided drainage offers the advantage of internal drainage, potentially alleviating catheter-related risks. However, EUS-guided gallbladder drainage requires a high degree of expertise. There are reports of percutaneous cholecystostomy being converted into internal drainage using endoscopic approaches. We report two cases of percutaneous cystic duct stenting.